EKSPLOITASI KAPITALISME TERHADAP PEREMPUAN; : Sebuah Kritik Ideologi - Akmal Saputra (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
This article is actually criticizing the regime of capitalism that has exploited Indonesian women. Today's capitalism is a manifestation of globalization called advanced or postmodern capitalism, globalization has had a tremendous impact on the lives of Indonesians in the social, economic, political, cultural, health and religious fields, both positive and negative. In this artkkel the author also describes the impact of globalization and criticizing the regime of capitalism that exploits women, in other words women "sold" for the business interests of capitalism, for example women become advertisement stars, both in television media and also print media, women become SPG (Sales promotion girls) in some capitalist companies, women work for a long time, the company does not pay attention to women's health conditions and unworthy salaries. Women become sex object (localization) for business continuity of capitalism. In this article the author judges the state (state) has affiliated with capitalism. Capitalism has sold women's bodies for business purposes, whereas they should be the domain of privacy rather than public consumption.